2019
DOI: 10.1302/1863-2548.13.180013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of impaired selective motor control on gait in children with cerebral palsy

Abstract: Purpose Spastic cerebral palsy (CP) is characterized by four neuromuscular deficits: weakness, short muscle-tendon unit, muscle spasticity and impaired selective motor control (SMC). We examined the influence of impaired SMC on gait in children with bilateral spastic CP. Delineating the influence of neuromuscular deficits on gait abnormalities can guide surgical and therapeutic interventions to reduce long-term debilitating effects of CP. Methods The relationship between impaired SMC and gait was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The physician rating score, a clinical physical examination assessment for children with CP, was also found to have high intraobserver but poor interobserver reliability. 4 Gait temporal-spatial parameters are readily measured in clinics, and studies have identified characteristic temporal-spatial parameters associated with neuromuscular deficits in spastic CP including: impaired selective motor control, 6 spasticity, 7 and muscle stretch characteristics. 8 In the last decade, the emergence of magneto-inertial units have been developed for the step-by-step estimation of the gait temporal-spatial parameters to assess gait and are increasingly being used in the clinical setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The physician rating score, a clinical physical examination assessment for children with CP, was also found to have high intraobserver but poor interobserver reliability. 4 Gait temporal-spatial parameters are readily measured in clinics, and studies have identified characteristic temporal-spatial parameters associated with neuromuscular deficits in spastic CP including: impaired selective motor control, 6 spasticity, 7 and muscle stretch characteristics. 8 In the last decade, the emergence of magneto-inertial units have been developed for the step-by-step estimation of the gait temporal-spatial parameters to assess gait and are increasingly being used in the clinical setting.…”
mentioning
confidence: 99%
“…The physician rating score, a clinical physical examination assessment for children with CP, was also found to have high intraobserver but poor interobserver reliability . Gait temporal‐spatial parameters are readily measured in clinics, and studies have identified characteristic temporal‐spatial parameters associated with neuromuscular deficits in spastic CP including: impaired selective motor control, spasticity, and muscle stretch characteristics …”
mentioning
confidence: 99%
“…(5)(6)(7)(8) A significant correlation between scores on the Selective Control Assessment of the Lower Extremities (SCALE) (9) and impaired gait has been found in children with CP. (2,9) These findings suggest that a crouch gait pattern may be related to impaired neuromuscular control and this might play a crucial role in the persistence of a flexed gait pattern.…”
mentioning
confidence: 86%
“…2.5/1000. (1) The damage in the central nervous system causes muscle weakness, shortening of muscle-tendon units, muscle spasticity and impaired selective motor control (SMC) (2,3) which results in gait limitations to a varying degree, as classified by the GMFCS-level. (4) One of the major gait difficulties is crouch gait.…”
mentioning
confidence: 99%
“…2.5/1000. (1) The damage in the central nervous system causes muscle weakness, shortening of muscle-tendon units, muscle spasticity and impaired selective motor control (SMC) (2,3) which results in gait limitations to a varying degree, as classified by the GMFCS-level. (4) One of the major gait difficulties is crouch gait.…”
mentioning
confidence: 99%